A Systematic Literature Review of Morphological Characterization of Banana Plants in Indonesia: A Bibliometric Analysis - Bambang Hariyanto; Irfan Suliansyah; Yusniwati Yusniwati; Agus Sutanto (Agrotechnology Research Journal, 2025)
Banana plants have a wide genetic diversity in Indonesia, but research on the morphological characterization of this fruit is limited. The purpose of this study was to conduct a systematic literature review on scientific trends, production, and knowledge, specifically the morphological characterization of the banana plant in Indonesia. An examination of 290 published documents in the Google Scholar database from 2012 to 2022 was carried out for this purpose. To reveal the overall trend of this topic, the co-occurrence of keywords was visualized and studied using VOSviewer software. The study findings revealed a linear increase in research trends over the years regarding the diversity of banana cultivars in some regions of Indonesia. Bibliometric mapping identified several primary research focuses, including the identification and characterization of the distinctive morphological diversity of banana plants, the utilization of various plant parts (such as leaves, stems, humps, and peels), as well as the analysis of nutritional composition and physical properties of processed products. Through overlay and density visualization, this study concludes that research on the morphological characterization of banana plants in Indonesia still holds extensive potential for future development to support the breeding of new superior varieties.